2014
DOI: 10.1380/ejssnt.2014.136
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigations for the Formation of InN/GaN(0001) Heterostructures

Abstract: The formation processes of InN/GaN heterostructures on GaN(0001) substrate are investigated by means of our ab initio-based approach and Monte Carlo (MC) simulations. Our ab initio calculations reveal that even under Ga-rich conditions the pseudo-(1×1) surface consisting of In in the first layer and Ga in the second layer is more stable than that of Ga in the first layer and In in the second layer. Furthermore, the calculated surface phase diagrams demonstrate that the pseudo-(1×1) surface with In-Ga metal lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It should be noted that the (4 × 3) with two In‐As and one As dimers and that with three In‐As dimers are less stable than the c(4 × 4) with two In‐As and one As dimers. These findings suggest that the growth of submonolayer InAs(001) before the (2 × 4) formation should be investigated on the c(4 × 4) with two In‐As and one As dimers at θ ≥ 0.88 ML instead of the (4 × 3) with two In‐As and one As dimers considered in our previous calculations . This gives one possible interpretation for the discrepancy between STM observations and our previous calculations.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…It should be noted that the (4 × 3) with two In‐As and one As dimers and that with three In‐As dimers are less stable than the c(4 × 4) with two In‐As and one As dimers. These findings suggest that the growth of submonolayer InAs(001) before the (2 × 4) formation should be investigated on the c(4 × 4) with two In‐As and one As dimers at θ ≥ 0.88 ML instead of the (4 × 3) with two In‐As and one As dimers considered in our previous calculations . This gives one possible interpretation for the discrepancy between STM observations and our previous calculations.…”
Section: Resultsmentioning
confidence: 58%
“…Kratzer et al showed that the (2 × 3) reconstruction can be regarded as the main building unit of the InAs WL. We have investigated the InAs(001)‐WL surface structures using ab initio‐based approach incorporating growth conditions such as temperature and beam equivalent pressure . Our previous studies elucidate that the InAs(001)‐(8 × 3) WL surface with In 0.375 Ga 0.625 As interface appears after 0.63 ML InAs deposited on the GaAs(001)‐c(4 × 4)α.…”
Section: Introductionmentioning
confidence: 99%
“…For example, polytypism in AlN grown on 4H-SiC (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) as a function of III/V ratio in addition to temperature and gas pressure has been clarified by using the chemical potential analysis [128]. The distinctive atomic arrangements were found to appear in subsequent adsorption of Al and N atoms after N and Al predepositions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that N atoms can be incorporated on the pseudo-(1 Â 1) surface by 2.3 ML at growth conditions. This is because the strained In-N interatomic bonds are effectively relaxed at the surface with small amounts of N deposition such as 1.7 ML, whereas N covering the surface induces the substitution between the topmost In and subsurface Ga to decrease strain in both Ga-N and In-N bonds [126]. The results for the In composition in each layer, varying the amount of N deposition obtained by the MMC simulation using ab initio data, are shown in Figure 11.34 for 1.7 and 2.3 ML depositions of N to elucidate the formation of InN/GaN heterostructures.…”
Section: Growth On Ingan Wetting Layer Surfacesmentioning
confidence: 99%